Comparative analysis of the efficiency of the Broken Tool Remover-Pen versus Zumax kit in the removal of fractured NiTi files from the root canal system. An in vitro study - Abdelhamied Yousef Saad; Farah T. Baraktat; Mohamed I. Attia (Wolters Kluwer Medknow Publications, 2024)
Introduction: Removal of a broken instrument may result in excessive dentin destruction and eventual tooth extraction. Therefore, the aim of this study is to evaluate the success of the Broken Tool Remover (BTR)-Pen system versus the Zumax kit in the retrieval of separated rotary files from the root canals, root canal volume changes, and retrieval time. Materials and Methods: Forty mandibular first molars were used in this investigation. Mesiobuccal canals were instrumented by ProTaper Next Rotary System up to a standard apical size 20/40 taper. Five mm of X2 file size 25/60 taper was fractured at a level of 3 mm apical to canal orifice. Teeth were randomly divided into two groups, 20 samples each. In Group A, fractured instruments were retrieved by utilizing BTR-Pen. In Group B, fractured files were retrieved using a Zumax kit. The success rate (%), as well as the postretrieval volumetric canal changes (mm3) using cone-beam computed tomography, and the retrieval time (min) were calculated in both groups. Results: The success rate of the separated fragment retrieval in Groups A and B was 80% and 90%, respectively, with no significant difference (P = 0.31). Moreover, concerning canal volume changes, there was a significant difference (P = 0:001) in comparison between the pre- and postretrieval volume changes in both groups. Group A showed significant lower changes (P = 0.0051) in root canal volume than Group B. Furthermore, the mean time ± standard deviation of retrieval in Group A was 29.56 ± 4.09 min, whereas in Group B, it was 23.29 ± 7.15 min with a significant difference (P = 0.00) between the two groups. Conclusion: Both devices were efficient and successful in retrieving separated rotary files. The utilization of the Zumax kit resulted in greater dentin loss but faster regarding time of retrieval.